Potassium 4-iodylbenzenesulfonate: preparation, structure, and application as a reagent for oxidative iodination of arenes - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Yusubova R. Ya. Roza Yavidovna; Nemykin V. N.; Maskaev A. V.; Geraskina M. R.; Kirschning A.; Zhdankin V. V. Viktor Vladimirovich (2012, 2012)
Title screen